EVALUATION OF LOCAL GOVERNMENT POLICIES IN WASTE MANAGEMENT IN NORTH MOROWALI REGENCY - Herry Yohanes Pinontoan; Irfan Mufti; Dandan Haryono (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Abstract This study aims to evaluate local government policies on waste management in North Morowali Regency based on William N. Dunn's (1994) policy evaluation theory, which includes four main indicators: effectiveness, efficiency, responsiveness, and policy accuracy. The research method used is a descriptive qualitative approach with data collection through in-depth interviews, observations, and reviews of regional policy documents. The results of the study indicate that waste management policies in North Morowali have not been fully effective in achieving the goals of waste reduction and handling, mainly due to limited facilities, minimal processing innovation, and low community participation. In terms of efficiency, budget use is still dominated by operational activities, while allocations for the development of 3R-based programs are still low. The responsiveness aspect is also weak due to the lack of community involvement in policy planning and implementation, while policy accuracy has not fully adopted the principles of a circular economy oriented towards sustainability. These findings indicate that waste management policies in North Morowali are still conventional and have not been able to optimally integrate social, economic, and environmental dimensions. Therefore, improvements to policies based on good environmental governance are needed through increased institutional capacity, multi-stakeholder collaboration, and strengthening community participation in sustainable waste management.